1999
DOI: 10.1116/1.590805
|View full text |Cite
|
Sign up to set email alerts
|

Influence of active nitrogen species on high temperature limitations for (0001_) GaN growth by rf plasma-assisted molecular beam epitaxy

Abstract: High temperature limitations for GaN growth by rf-plasma assisted molecular beam epitaxy: Effects of active nitrogen species, surface polarity, hydrogen, and excess Ga-overpressure J.The relation of active nitrogen species to high-temperature limitations for (0001) GaN growth by radio-frequencyplasma-assisted molecular beam epitaxy A reduced growth rate for plasma-assisted molecular beam epitaxy GaN growth often limits growth to temperatures less than 750°C. The growth rate reduction is significantly larger th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 24 publications
1
34
0
1
Order By: Relevance
“…Several studies in the deposition of GaN using N 2 plasmas have revealed that the properties of the deposited thin films depend on the relative flux of N and excited N 2 (N 2 *) to the surface during growth. [7][8][9] Specifically, N 2 * is thought to be more desirable for GaN growth since it facilitates higher film growth rates at lower substrate temperatures with significantly improved electrical properties in comparison to growth with a predominantly atomic N flux. 7,8 Thus, there is a need to simultaneously characterize the N and N 2 * fluxes impinging on the substrate to determine the role of these precursors during deposition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in the deposition of GaN using N 2 plasmas have revealed that the properties of the deposited thin films depend on the relative flux of N and excited N 2 (N 2 *) to the surface during growth. [7][8][9] Specifically, N 2 * is thought to be more desirable for GaN growth since it facilitates higher film growth rates at lower substrate temperatures with significantly improved electrical properties in comparison to growth with a predominantly atomic N flux. 7,8 Thus, there is a need to simultaneously characterize the N and N 2 * fluxes impinging on the substrate to determine the role of these precursors during deposition.…”
mentioning
confidence: 99%
“…[7][8][9] Specifically, N 2 * is thought to be more desirable for GaN growth since it facilitates higher film growth rates at lower substrate temperatures with significantly improved electrical properties in comparison to growth with a predominantly atomic N flux. 7,8 Thus, there is a need to simultaneously characterize the N and N 2 * fluxes impinging on the substrate to determine the role of these precursors during deposition. In this letter, we report the use of modulatedbeam line-of-sight threshold ionization mass spectrometry ͑LOS-TIMS͒ to measure the absolute densities of N and N 2 * in an N 2 plasma.…”
mentioning
confidence: 99%
“…Two rf-plasma sources were used to produce active nitrogen, an Oxford Applied Research CARS-25 (Oxfordshire, UK) and a Veeco Instruments Inc. (formerly Applied EPI) (St. Paul, MN) Unibulb source. Characterization of these sources has been extensively reported elsewhere [1][2][3][4]. The Oxford source produced primarily atomic nitrogen as the active species under our operating conditions, while the EPI source produced primarily metastable molecular nitrogen corresponding to the A u 3 Σ + metastable state [5,6] with a significant atomic nitrogen component remaining.…”
Section: Methodsmentioning
confidence: 99%
“…Vaudo et al also studied the two type plasma sources [7,8] and showed details of the atomic N emission lines [8]. Myers et al compared several RF plasma cells such as an Oxford Applied Research source and an EPI Vacuum Unibulb source [9]. They showed that the smaller size of hole diameter, or aperture, of an orifice reduced the ion flux and increased the contribution from atomic N. The high efficiency of the production of atomic N could be realized at higher pressure with the small holes.…”
Section: Introductionmentioning
confidence: 96%